ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI DENGAN MENGGUNAKAN METODE VARIABEL COSTING UNTUK MENENTUKAN HARGA JUAL PRODUK: Studi Kasus Pada CV Sumber Kasih - Intan, Theresia Maldiana; Marselina, Apriana; Kapa, Sesilianus (Program Studi Akuntansi Universitas Flores, 2025)
This study aims to determine the calculation of the cost production using the variabel costing method in determining the selling price at CS Sumber Kasih. This research is qualitative and quantitative research. Data collection techniques used are observation, interviews, documentation, literature study. The data analysis technique used in this research is descriptive analysis. This results of this study indicate that there are difference in the calculation of the production and selling price between CV Sumber Kasih companies and the variable costing method where the calculation using the variable costing method is higher than the company's method.